New educational approach to train the micro, small and medium enterprises for the human resources that Peru needs for sustainable economic development in the XXI century - García Monterroso, Amador Velásquez (2021)
The National Plan of Productive Diversificafion (DS 004-Produce 2014) did not accomnplished its goal. This handicap took us far away from the sustainable development 21st century vis a vis to the high competitiveness of the international environment. Peru´s dependence on its main commodities, determines that its production of good and services is of low profability. The high change giving more value added to the Peruvian goods and services exportation is a must. To do that, Peruvian MIPYMEs must be able to become high level competitiveness enterprises, but their human resources are not able to get that goal, so the Fair Knowledge Trilogy of the Economy (KeT) pretend to be the respond.